Intrarenal hemodynamics and kidney function in pheochromocytoma and paraganglioma before and after surgical treatment. (4th May 2021) - Januszewicz, Magdalena; Dobrowolski, Piotr; Januszewicz, Andrzej; Warchoł-Celińska, Ewa; Jóźwik-Plebanek, Katarzyna; Motyl, Daria; Kabat, Marek; Pęczkowska, Mariola; Michałowska, Ilona; Ambroziak, Urszula; Toutounchi, Sadegh; Gałązka, Zbigniew; et al.
Abstract: Purpose: Current evidence regarding renal involvement in pheochromocytoma and paraganglioma (PPGL) is scant. More accurate diagnostic methods, such as renal Doppler ultrasound for intrarenal hemodynamic studies, may provide more detailed information on renal function. It might be postulated that renal function in PPGL patients might be altered by high blood pressure and excess secretion of catecholamines. The aim of this prospective study was to assess intrarenal blood flow parameters in PPGL patients included in the prospective monoamine-producing tumour (PMT) study and to evaluate the effects of normalisation of catecholamine production after surgical treatment on long-term renal function. Materials and methods: Seventy consecutive patients (aged 46.5 ± 14.0 years) with PPGL were included. Forty-eight patients from the PMT study cohort, matched for age, gender, blood pressure level and presence of hypertension, served as a control group. Renal artery doppler ultrasound spectral analysis included mean resistance index (RRI) and pulsatility index (PI). Forty-seven patients completed 12 months follow-up. Results: There were no differences in renal parameters such as RRI, PI and kidney function between PPGL and non-PPGL patients as assessed by renal ultrasound, serum creatinine, eGFR and albumin excretion rate. No correlations between kidney function parameters, intrarenal doppler flow parameters and plasma catecholamines were observed in PPGL patients. At 12 months after surgery, no differences in creatinine level, eGFR, albumin excretion rate, RI and PI were found as compared to baseline results. Conclusions: In contrast to patients with other forms of secondary hypertension, our study did not show differences in intrarenal blood flow parameters and renal function between PPGL and non-PPGL subjects. Intrarenal hemodynamics and renal function did not change after normalisation of catecholamine levels by surgical treatment.